2021
DOI: 10.1101/2021.03.12.21253444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy among undergraduate medical students: results from a nationwide survey in India

Abstract: COVID-19 vaccine was launched in India on 16 January 2021, prioritizing health care workers which included medical students. We aimed to assess vaccine hesitancy and factors related to it among undergraduate medical students in India. An online questionnaire was filled by 1068 medical students across 22 states and union territories of India from 2 February to 7 March 2021. Vaccine hesitancy was found among 10.6%. Concern regarding vaccine safety and efficacy, hurried testing of vaccines prior to launch and lac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 21 publications
5
31
0
Order By: Relevance
“…The findings of Verger et al (2021) were a bit close to what had been found in Malta (22%), Portugal (21%), Germany (20%), the Netherlands (19%), and Italy (19%) [38,39]. On the other hand, the studies that sampled general university students showed a wide range of hesitancy about COVID-19 vaccines, ranging between Egypt (46%), Jordan (25.5%), Malta (25.3%), the USA (19.3%), and India (10.6%) [21,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Verger et al (2021) were a bit close to what had been found in Malta (22%), Portugal (21%), Germany (20%), the Netherlands (19%), and Italy (19%) [38,39]. On the other hand, the studies that sampled general university students showed a wide range of hesitancy about COVID-19 vaccines, ranging between Egypt (46%), Jordan (25.5%), Malta (25.3%), the USA (19.3%), and India (10.6%) [21,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…District level data are unavailable as people do not have access to data about vaccination centers, daily vaccination, or adverse events in their district. In the case of India, even the Aarogya Setu app which is supposed to have all the needed information about the pandemic and vaccination does not have this important information (Jain et al, 2021). Another factor is lack of limited information about side effects of vaccines (Mahmud et al, 2021;Jain et al, 2021).…”
Section: Lack Of Sufficient and Transparent Informationmentioning
confidence: 99%
“…Since it has been just a few months before they came out, people are afraid that the vaccines can have adverse long-term effects on their health if they get vaccinated (Jain et al, 2021). They are also afraid of short-term effects because of limited information (Mehdi, 2021).…”
Section: Lack Of Sufficient and Transparent Informationmentioning
confidence: 99%
See 2 more Smart Citations